2009
DOI: 10.1007/s10681-008-9869-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular markers associated with sugar-related traits in a Saccharum interspecific cross

Abstract: The cultivated sugarcane (Saccharum spp. hybrids, 2n = 100-130) is one crop for which interspeciWc hybridization involving wild germplasm has provided a major breakthrough in its improvement. Few clones were used in the initial hybridization event leading to a narrow genetic base for continued cultivar development. Molecular breeding would facilitate the identiWcation and introgression of novel alleles/genes from the wild germplasm into cultivated sugarcane. We report the identiWcation of molecular markers ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This narrow genetic base could restrict advancement in sugarcane breeding programs. A interspecific hybridization strategy used in the early 1900s introgessed genes and traits of choice from wild relatives into sugarcane cultivars to increase the genetic variability, resulting in significant improvements in sugarcane breeding and genetics [105]. For this introgression, plants of the F 1 and first backcross (BC 1 ) generations receive diploid gametes from a female S. officinarum, and haploid gametes from male S. spontaneum.…”
Section: Segregation Analysismentioning
confidence: 99%
“…This narrow genetic base could restrict advancement in sugarcane breeding programs. A interspecific hybridization strategy used in the early 1900s introgessed genes and traits of choice from wild relatives into sugarcane cultivars to increase the genetic variability, resulting in significant improvements in sugarcane breeding and genetics [105]. For this introgression, plants of the F 1 and first backcross (BC 1 ) generations receive diploid gametes from a female S. officinarum, and haploid gametes from male S. spontaneum.…”
Section: Segregation Analysismentioning
confidence: 99%
“…For example, Wei et al (2006) found that 11 AFLP markers could account for 59% of smut rating variation. For a biparental population, Alwala et al (2009) reported that 35.5%-48.4% of phenotypic variation for Brix or 22.1%-36.2% of phenotypic variation for pol could be explained by five to seven markers.…”
Section: Significant Markersmentioning
confidence: 99%
“…The highly heterozygous nature of sugarcane allows one to use the F 1 progeny of two highly heterozygous parents or the selfed progeny of a clone as the mapping population provided the progeny segregates for the trait in question (Selvi and Nair 2010). Linkage mapping has been done in sugarcane using low frequency marker alleles as it is possible to detect their segregation in a multiallelic system, and partial genetic maps have been produced for S. spontaneum (Al-Janabi et al 1993;daSilva et al 1993daSilva et al , 1995Ming et al 1998), S. officinarum (Mudge et al 1996;Guimaraes et al 1997;Aitken et al 2006), interspecific hybrids (Daugrois et al 1996;Ming et al 2001;Alwala et al 2009) and modern cultivars of sugarcane (Hoarau et al 2001;Edme et al 2006;Garcia et al 2006;Raboin et al 2006;Alwala et al 2008;Pastina et al 2012). However, the predominant mapping strategy based on single dose loci involves a biased genome sampling (Garcia et al 2013).…”
Section: Introductionmentioning
confidence: 99%